Seasonal and post-rainfall dynamics of soil CO2efflux in wheat and peanut fields - Chompunut Chayawat (2018)
It is crucial to understand the effect of rainfall on soil CO2efflux and the factors that control efflux. This paper investigates the influence of rainfall events on soil CO2efflux from wheat and peanut fields by using high-frequency soil gradient efflux method and long term automated soil chamber measurements. Results show soil CO2efflux decreased during and immediately after rainfall events, which was related to reduce gaseous diffusivity as a response. A few hours after rainfall, a significant increase in soil CO2efflux was observed, the increased rates of soil CO2efflux were different among the growth stages of peanut. A significant correlation between soil water content and soil CO2efflux after rainfall was found, suggesting that soil water content has consequence for short-term losses of soil CO2efflux after rainfall. The present study suggests that high-frequency soil CO2efflux measurements should be made to capture large pulses in CO2emissions to adequately model carbon-water cycling from agricultural soils to the atmosphere.